Effect of CuO/ZnO/FTO electrode properties on the performance of a photo-microbial fuel cell sensor for the detection of heavy metals. (September 2022) - Lu, Yue; Hu, Xingxin; Tang, Lin; Peng, Bo; Tang, Jin; Zeng, Taotao; XunkuoZhang,; Liu, Qian
Abstract: The development of sustainable, low-cost and responsive technology for heavy metals detection in wastewater is crucial. In this study, by combining CuO/ZnO photocathode with microbial anode, a novel photo-microbial fuel cell (PMFC) sensor was developed. The self-powered PMFC was performed under light and dark condition for heavy metals detection. Compared with MFC sensor, PMFC sensor showed a wider detection range (0.1–4 mg L −1 of Cd 2+ and 10–80 mg L −1 of Cu 2+ ). The improved performance in sensing limit and sensitivity was mainly attributed to the intimate P–N heterojunctions formed in CuO/ZnO, which accelerated the electron transport between the photocathode and the microbial anode. Besides, the toxicity of five heavy metals tested in PMFC was shown as Cd 2+ >Cr 6+ >Zn 2+ >Hg 2+ >Cu 2+ . This study has taken advantage of the characteristics of PMFC and facilitated its application in heavy metals detection, which provides a new approach for the development of biosensors. Graphical abstract: Image 1 Highlights: A novel photo microbial fuel sensor was designed. The photo microbial fuel sensor was self-powered and repeatable. Synergistic interaction improved the detection sensitivity. The mechanism of the photo-microbial fuel cell sensor was proposed.